PENGARUH AUDITOR INTERNAL PEMERINTAH, SISTEM PENGENDALIAN INTERNAL DAN MORALITAS APARAT TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris pada SKPD Kota Medan - Wahid Qadri Damanik; Hardi Hardi; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Study this aims to examine the effect of internal government auditor, internal control system and apparatus morality on the tendency of accounting fraud in Medan SKPD. The sample use were 56 respondens. The type of data used is primary data by using questionaire method of data collection. The method of data analysis used in this study is purposive sampling with the help of software SPSS version 20.0. The result showed that : internal government auditor, internal control system and work and apparatus morality has significant influence on the tendency of accounting fraud.Keywords :Internal government auditor, internal control system,apparatus moralitiy, tendency accounting fraud.